Sᴏʟᴠᴇ:
![\frac{x - b - c}{a} \: \: + \frac{x - c - a}{c} \: \: + \frac{x - a - b}{c} = 3 \frac{x - b - c}{a} \: \: + \frac{x - c - a}{c} \: \: + \frac{x - a - b}{c} = 3](https://tex.z-dn.net/?f=+%5Cfrac%7Bx+-+b+-+c%7D%7Ba%7D+++%5C%3A++%5C%3A++%2B++%5Cfrac%7Bx+-+c+-+a%7D%7Bc%7D++%5C%3A++%5C%3A++%2B++%5Cfrac%7Bx+-+a+-+b%7D%7Bc%7D++%3D+3)
ᴡᴀɴᴛ ϙᴜᴀʟɪᴛʏ ᴀɴsᴡᴇʀs!!
Answers
Answered by
187
⠀
ㅤ
⠀
ㅤ
⠀
ㅤ
⠀
ㅤ
⠀
ㅤ
+
+![[ \frac{(x - a - b)- 1}{c} ]=0 [ \frac{(x - a - b)- 1}{c} ]=0](https://tex.z-dn.net/?f=%5B+%5Cfrac%7B%28x+-+a+-+b%29-+1%7D%7Bc%7D+%5D%3D0)
⠀
ㅤ
ㅤ
ㅤ
- Take out
as common
⠀
ㅤ
⠀
ㅤ
⠀
ㅤ
⠀
ㅤ
ㅤ
ㅤ
ㅤ
ㅤHope it Helps uh Dear!! ❤
ㅤ
ㅤ
ㅤᕼᗩᑭᑭY ᒪᗴᗩᖇᑎíᑎᘜ ☃️
Similar questions